2, 2, 2-Trifluoroethyl-thiadiazines: a patent evaluation of WO2016023927. (1st December 2016) - Dotsenko, Victor V.; Chigorina, Elena A.; Krivokolysko, Sergey G.
ABSTRACT: The Alzheimer's disease (AD) is acknowledged as the most common type of dementia in aging adults. It is characterized by the formation of intracellular neurofibrillary tangles and extracellular amyloid plaques. The latter insoluble deposits mainly consist of β-amyloid peptides (Aβ), which are the derivatives of the amyloid precursor protein (APP). The formation of neurotoxic Aβ-peptides involves the cleavage of APP with beta-secretase enzyme (beta-site APP cleaving enzyme 1, BACE1) so the potential of BACE1 inhibitors as therapeutic agents for AD is now drawing much attention. The patent application WO2016023927 reports the preparation of new 1, 2, 4-thiadiazine inhibitors of BACE1 activity and their use as therapeutically active substances. Some of the new compounds are claimed to be good inhibitors with the IC50 values in the 0.000292–0.134165 μM range. Several pharmaceutical preparations based on these compounds are proposed for possible treatment and prevention of AD. Expert opinion: In light of the novelty from the chemical point of view and improved biological activity, the reported 2, 2, 2-trifluoroethylthiadiazines could be considered as promising BACE1 inhibitors. However, the available data are insufficient to make a recommendation if these compounds can be considered as drug candidates. Further studies with a larger number of compounds are required. The compounds described in the patent have to be characterized more thoroughly from the chemical viewpoint (e.g., by means of IR, 1 H and 13 C NMR spectroscopy, X-ray crystallography), especially as regards stereochemical details.